The influences of cultural characteristics in writing English: Perspectives from multilingual learners - Rahma Fitriana (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Research studies have discussed about potential influences of the learners’ cultural characteristics on writing in the first language to writing in English. However, only limited bodies of literature highlighted the phenomenon from the learners’ perceptions and experiences. Using a case study approach, the current study interviewed two ESL writing students who come from Indonesia and went to Australian high schools. The audio-recorded interviews were analyzed using thematic content analysis. Findings of the study show that writing in their first and additional languages as well as writing in English do not have significant differences, despite a few difficulties dealing with English grammar. There were several other factors which could also determine students’ performance in writing classes, such as teachers’ instruction, teachers’ feedback, classroom environment, and home literacy practices. The participants’ experiences have demonstrated that intercultural rhetoric (IR) better approached ESL writers as it views culture in complex and dynamic perspectives, and acknowledges learners’ different cultural backgrounds. The learners expect that the writing teachers aware of potential cultural differences in their writing and provide more intercultural opportunities. This article also highlights the IR-informed pedagogical approach which can potentially utilize the strengths of multicultural and multilingual writers in ESL classrooms.